Regulatory interventions in response to noncompliance with mandatory derivatives disclosure rules - BHATTACHARYA, Neil (Institutional Knowledge at Singapore Management University, 2022)
We investigate regulatory actions in response to violations of mandatory derivatives disclosure rules (SFAS 161) and the outcomes of these regulatory interventions using a hand-collected sample of derivatives disclosures. Derivatives are used by nearly two-thirds of U.S. nonfinancial firms, and they are one of the most complex types of financial contracts. Consequently, inadequate derivatives disclosures could pose significant challenges to financial statement users in assessing the risk and financial health of enterprises. First, we document that firms with high proprietary and agency costs are less likely to comply with SFAS 161. Next, by examining derivatives-related SEC comment letters, we further show that this noncompliance significantly increases the likelihood of receiving a comment letter. We also find that comment letter resolution is longer for firms with strong proprietary motivations than for those with strong agency incentives. Finally, we find that compliance with regard to derivatives disclosures following comment letter resolution improves for firms with high agency costs but not for firms with high proprietary costs. Collectively, our results imply that, when derivatives-related proprietary costs are high, benefits of noncompliance likely outweigh the costs. Moreover, the SEC’s review effectiveness depends crucially on whether firms’ initial motivation for noncompliance is proprietary versus agency.